The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/mrc.4826
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurement of deposit layer formation during skim milk filtration by MRI

Abstract: Filtration and separation via membranes are key processes in food processing. One major application of membrane filtration is in the dairy industry, aiming for the separation of different milk proteins. The various chemical components of milk possess different physiochemical properties and can be used most effectively in food processing if they are separately available and remain in their native state. Microfiltration of skim milk allows a fractionation of the milk proteins casein and whey by size. A deposit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
1
16
0
1
Order By: Relevance
“…The MIONs with a mean diameter of 100 nm are composed of iron oxide clusters embedded in a matrix of dextran and are coated with casein proteins to be chemically compatible with the feed. In previous studies [21][22][23][24][25]27,28], it was shown that the contrast agent is embedded in the deposit layer and does not diffuse back into the feed solution separately from the deposit nor significantly permeates the membrane. To confirm and investigate the behaviour of these MIONs, the deposit layer was taken out of the hollow fibre membrane after filtration with MIONs and put into a glass tube filled with skim milk, also including the contrast agent.…”
Section: Mri Contrast Agentmentioning
confidence: 99%
See 4 more Smart Citations
“…The MIONs with a mean diameter of 100 nm are composed of iron oxide clusters embedded in a matrix of dextran and are coated with casein proteins to be chemically compatible with the feed. In previous studies [21][22][23][24][25]27,28], it was shown that the contrast agent is embedded in the deposit layer and does not diffuse back into the feed solution separately from the deposit nor significantly permeates the membrane. To confirm and investigate the behaviour of these MIONs, the deposit layer was taken out of the hollow fibre membrane after filtration with MIONs and put into a glass tube filled with skim milk, also including the contrast agent.…”
Section: Mri Contrast Agentmentioning
confidence: 99%
“…The protein deposit on the membrane can also be measured exploring the native MRI contrast, i.e., without contrasting agent. However, a better contrast between feed and deposit is achieved because of the high transverse relativity of MIONs [25]. Lower signal intensities are induced because of the dominantly transverse paramagnetic relaxation enhancement of the nanoparticles.…”
Section: Mri Contrast Agentmentioning
confidence: 99%
See 3 more Smart Citations